Analisis Pengaruh Faktor Sosial Ekonomi melalui Curahan Jam Kerja Terhadap Pendapatan Perempuan Pekerja Sektor Informal di Desa Kukuh Kecamatan Marga - Dewi, Ni Luh Putu Septeri Kusuma; Tisnawati, Ni Made (Peneliti.net, 2024)
Kukuh Village is a village with the highest rate of poor household within Marga District with the amount of 1.471 people with the largest population composition in Marga District which includes six hamlets with a population of 5.789 people. The purpose of this study are 1) to analyze the influence of age, work experience, number of dependents, and customary activities on the amount of working hours of women workers in the informal sector in Kukuh Village, Marga District. 2) To analyze the influence of age, work experience, number of dependents, and customary activities on the income of women workers in the informal sector in Kukuh Village, Marga District. 3) To analyze the influence of age, work experience, number of dependents, and customary activities which indirectly influence women’s income through the amount of working hours of worker in informal sector businesses in Kukuh Village, Marga District. This study uses primary data, namely by distributing questionnaires to informal sector women workers in Kukuh Village. The respondents of this study were women informal sector workers in Kukuh Village, with a total sample of 90 people with sample determination using snowball sampling. The type of data used is quantitative data with primary data sources. Study data collection was carried out by means of observation and structured interviews. Data processing was analyzed using descriptive analysis techniques, path analysis and Sobel tests. The study results showed that the variables age, work experience, number of dependents had a positive and significant effect on the amount of working hours and customary activities had a significant negative effect on the amount of working hours. Meanwhile, the variables age, work experience, number of dependents have a positive and significant effect on women's income and customary activities have a significant negative effect on women's income. The amount of working hours does not mediate the relationship between age, work experience, number of dependents, and customary activities on women's income in Kukuh Village, Marga District.